Molecular heterogeneity of glucose-6-phosphate dehydrogenase deficiency in neonates in Wuhan: Description of four novel variants - Shen, Shanshan; Xiong, Qian; Cai, Wenqian; Hu, Rui; Zhou, Bin; Hu, Xijiang (Frontiers in Genetics, 2022)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is one of the most common X-linked enzymopathies caused by G6PD gene variant. The aim of this study was to investigate the molecular epidemiological characteristic of the G6PD deficiency among newborn screening population in Wuhan region. A total of 430,806 healthy neonates in Wuhan area of China were screened for G6PD deficiency from November 2016 to December 2021. The positive samples were further detected with gene analysis. Among the 957 neonates with abnormal G6PD enzyme activity, the prevalence of G6PD deficiency in Wuhan was calculated as 0.22%. 38 genotypes were found and the top 5 frequency of G6PD gene variants were c.1388 G>A, c.1376 G>T, c.95 A>G, c.1024 C>T and c.871 G>A. Seven rare single variants (c.25C>T, c.152C>T, c.406C>T, c.497G>A, c.679C>T, c.854G>A and c.1057C>T) and two rare multiple variants (IVS-5 637/638T del/c.1311C>T/1365-13T>C and c.406C>T/c.1311C>T/1365-13T>C) were discovered in this study. In addition, four novel variants (c.49C>T, c.691G>A, c.857A>T and c.982G>A) were detected out in our cohort, which never been reported before. The result indicated that a rich diversity of G6PD genetic variants in Wuhan region, also had its own regional characteristic. Our data provided the basic knowledge for future prevention and research of G6PD deficiency and the findings will be useful for genetic counseling and prenatal diagnosis of G6PD deficiency in the Wuhan region.